Widespread pain and pain intensity in patients with early rheumatoid arthritis. A cross‐sectional comparison between smokers and non‐smokers - Marie‐Louise Karlsson; Ann‐Charlotte Elkan; Ingiäld Hafström (Wiley, 2019)
Abstract Aim The aim was to investigate if smoking status at time for diagnoses of rheumatoid arthritis was associated with pain intensity or pain spread. Design A cross‐sectional study conducted in 2012-2013. Methods Seventy‐eight patients, of whom 16 were current smokers and 62 never or previous smokers, with newly diagnosed rheumatoid arthritis were assessed as to pain intensity, widespread pain and disease activity. Results Of the participants, 56% had unacceptable pain, 77% had spread pain and 28% had chronic widespread pain. There were no differences in pain intensity, widespread pain or chronic widespread pain between smoking status groups. However, there was a positive association between pain intensity and disease activity, r = 0.52. Conclusion In this study, patients with early rheumatoid arthritis had a high‐frequency unacceptable pain and wide spread pain, irrespective of smoking status. However, we cannot exclude that the inflammatory‐associated pain overshadowed a possible negative effect of smoking.